(untitled) (Revista Multi-Ensayos, 2019)
The current society and the technological advance demand civil engineers not only with scientific-technical knowledge but endowed with humanistic and social knowledge reflected in their attitude and aptitude to handle interpersonal relationships. In addition, it is necessary that they are knowledge managers, able to face real problems, adapting to the demands and dynamic demands, with the perspective vision and expanded in their labor. Universities are facing a new environment that demands an academic quality work in education, a very complex task because it will have to give evidence to the society of their effort to a selective and increasingly competitive labor market. This essay study the professional profile of the civil engineer demanded by the society and that educational engineering institutions from a strategic, holistic, anthropocentric and systemic position are supposed to return as a product to todays society. In the Nicaraguan context, civil engineering contributes to the economic and social development, through the design, construction, and supervision of civil workings. Therefore, universities need to evaluate and structure the professional profile of the civil engineer, in order to respond to the demands of the environment.